Effect of physics education technology project simulation on improvement of retention ability of grade six learners in state of matter - Nkosi, Landiwe Beauty; Chinaka, Taurayi W.; Sondlo, Aviwe; Mpuangnan, Kofi N. (Edelweiss Applied Science and Technology, 2024)
Physics Education Technology Project (PhET) simulation gives students the opportunity to explore and experiment with scientific phenomena in a safe, virtual setting. This study investigated the effects of PhET improvement on the retention ability of grade six learners in state of matter (SOM). To achieve the aim of the study sixty-four grade six learners were considered from four randomly selected primary schools in Umkhanyakude District in KwaZulu-Natal province. The study utilized a quasi-experimental design with a non-equivalent pre-test, post-test, and delayed post-test approach. Data were collected using the Phase Change of Matter Test (PCMT) administered during the pre-test, post-test, and delayed post-test phases. Participants in the control group were taught using the traditional teacher-centered approach, while the experimental group was exposed to the SOM PhET simulation. The reliability coefficient of 0.75 was determined using Cronbach’s alpha reliability coefficient. The data were analyzed using descriptive statistics, including mean, median, standard deviation, and range, to summarize the pre-test, post-test, and delayed post-test scores for both groups. A paired samples t-test was also conducted for each group to compare the pre-test and post-test scores, as well as the post-test and delayed post-test scores, to assess whether there was a significant improvement in retention following the intervention. The findings indicated that using PhET as an intervention effectively enhanced conceptual understanding of SOM. There was a statistically significant difference in the retention ability after treatment with a PhET simulation, compared to the control group. Based on the findings, it is recommended that students actively interact with simulations rather than merely observing demonstrations. When students engage directly with these tools, they achieve a deeper understanding and improved learning outcomes.